A feedback regulation between ARF7‐mediated auxin signaling and auxin homeostasis involving MES17 affects plant gravitropism. Issue 7 (6th June 2022) - Zhang, Feng; Li, Cuiling; Qu, Xingzhen; Liu, Jiajia; Yu, Zipeng; Wang, Junxia; Zhu, Jiayong; Yu, Yongqiang; Ding, Zhaojun
ABSTRACT: Gravitropism is an essential adaptive response of land plants. Asymmetric auxin gradients across plant organs, interpreted by multiple auxin signaling components including AUXIN RESPONSE FACTOR7 (ARF7), trigger differential growth and bending response. However, how this fundamental process is strictly maintained in nature remains unclear. Here, we report that gravity stimulates the transcription of METHYL ESTERASE17 ( MES17 ) along the lower side of the hypocotyl via ARF7‐dependent auxin signaling. The asymmetric distribution of MES17, a methyltransferase that converts auxin from its inactive form methyl indole‐3‐acetic acid ester (MeIAA) to its biologically active form free‐IAA, enhanced the gradient of active auxin across the hypocotyl, which in turn reversely amplified the asymmetric auxin responses and differential growth that shape gravitropic bending. Taken together, our findings reveal the novel role of MES17‐mediated auxin homeostasis in gravitropic responses and identify an ARF7‐triggered feedback mechanism that reinforces the asymmetric distribution of active auxin and strictly controls gravitropism in plants. Abstract : AUXIN RESPONSE FACTOR 7 (ARF7) is essential for gravitropic responseS through regulation of auxin homeostasis. ARF7‐mediated auxin signaling stimulates the expression of METHYL ESTERASE17 ( MES17 ), which catalyses the conversion from methylated indole‐3‐acetic acid (IAA) to free IAA and amplifies auxin gradient formation in plant gravitropism.